Biocontrol of Alternaria alternata in cold-stored table grapes using psychrotrophic yeasts and bioactive compounds of natural sources - Torres Palazzolo, Carolina Andrea (2024)
Alternaria alternata is a common fungal pathogen causing postharvest decay in table grapes. This study addressed the potential of autochthonous yeasts and bioactive compounds of natural sources to act as biocontrol agents (BCAs) against A. alternata in cold-stored table grapes. With this purpose, 19 yeast capable of growing at 0–1 ◦C were isolated from the surface of Red Globe table grapes. These isolates, along with the pre-isolated strain Metschnikowia pulcherrima RCM2, were evaluated as BCAs in wounded berries. From these results, six yeast isolates were pre-selected to be combined with bioactive compounds of natural sources, like phenolic compounds(PCs) of side streams of wine industry, including bunch stem extract (BSE) (5–25 %), and cane extract (CE) (5–25 %), and functional polysaccharides from shrimp waste such as chitosan (CH) (0.5 %). Then, the biocontrol efficacy of combined treatments beyond individual ones was compared. The results revealed that 4 yeast isolates, namely M. pulcherrima RCM2 and ULA146, and Aureobasidium pullulans FUL14 and FUL18, were the most effective. However, when combined with the natural bioactive compounds, their efficacy against A. alternata did not increase significantly. Notably, ULA146 and FUL18 demonstrated a biocontrol efficacy of 36–37 %, comparable to that of the treatment with commercial doses of SO2, which only showed a 27 % reduction in the lesion diameter. These findings highlight the potential of using psychrotrophic yeasts as BCAs against A. alternata in cold-stored table grapes. Combining these yeast strains with BSE, CE and CH did not increase BCAs efficacy against this pathogen at the concentrations tested. The development of effective biocontrol strategies for A. alternata could contribute to reducing reliance on chemically synthesized fungicides, promoting sustainable practices, aiming to improve the quality and safety of cold-stored table grapes.